Tungsten carbide: A versatile additive to get trace alkaline-earth oxide impurities out of ZrB2 based ceramics. (1st April 2018) - Zou, Ji; Ma, Hai-Bin; D'Angio, Andrea; Zhang, Guo-Jun
Abstract: In this work, trace amounts of alkaline-earth oxide impurities (Mx Oy ), M = Mg, Ca and Al, are identified from different graded ZrB2 based ceramics. The reactions in Mx Oy -WC systems at high temperature are therefore investigated via X-ray diffraction and element analysis, which have been further supported by thermodynamic calculations. Since Mx Oy with low melting point deteriorates the high temperature performance of ceramics, the effective role of WC on strong ZrB2 -SiC-WC ceramics is re-considered: apart from the contribution on removing of ZrO2, WC serves as a versatile additive with capacity to remove different oxide impurities from the ceramic body. Graphical abstract: Image 1